2015
DOI: 10.1371/journal.pone.0137032
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-Mediated Inositol Lipid Signaling Plays Critical Roles in Regulation of Blebbing

Abstract: Cells migrate by extending pseudopods such as lamellipodia and blebs. Although the signals leading to lamellipodia extension have been extensively investigated, those for bleb extension remain unclear. Here, we investigated signals for blebbing in Dictyostelium cells using a newly developed assay to induce blebbing. When cells were cut into two pieces with a microneedle, the anucleate fragments vigorously extended blebs. This assay enabled us to induce blebbing reproducibly, and analyses of knockout mutants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…It will be interesting to learn how, for example, proteins localized to the cytosol, plasma membrane, MTOC, or the nucleus can all negatively regulate PI3K pathways. Two of the RAM proteins localizing to the MTOC (SepA and DSPA) provide further support for the importance of microtubules in regulating cell polarity, migration, and adhesion (28,(79)(80)(81). Moreover, almost all of the phenotypes can be suppressed by overexpression of dominant negative Rap1 which is thought to be a regulator in multiple pathways involved in chemotaxis.…”
Section: Regulators Of Adhesion and Motility Reveal Multiple Points Ofmentioning
confidence: 82%
“…It will be interesting to learn how, for example, proteins localized to the cytosol, plasma membrane, MTOC, or the nucleus can all negatively regulate PI3K pathways. Two of the RAM proteins localizing to the MTOC (SepA and DSPA) provide further support for the importance of microtubules in regulating cell polarity, migration, and adhesion (28,(79)(80)(81). Moreover, almost all of the phenotypes can be suppressed by overexpression of dominant negative Rap1 which is thought to be a regulator in multiple pathways involved in chemotaxis.…”
Section: Regulators Of Adhesion and Motility Reveal Multiple Points Ofmentioning
confidence: 82%
“…Consistent with these observations, pharmacological inhibition of Myosin II and rho-associated protein kinase decreased neural crest cell blebbing and delamination (Berndt et al, 2008). Other experiments show that Myosin II function is required to promote bleb formation among gastrula stage mesodermal cells in zebrafish (Weiser et al, 2009) and in Dictyostelium (Sugiyama, Pramanik, & Yumura, 2015), presumably by increasing cortical tension and cytosolic hydrostatic pressure (Tinevez et al, 2009). Bleb formation in Dictyostelium is attributable to the focal disassembly of microtubules that likely stabilize membrane phosphatidylinositol 3,4,5-trisphosphate, a positive regulator of actin assembly (Sugiyama et al, 2015).…”
Section: Molecular Mechanismsmentioning
confidence: 55%
“…Other experiments show that Myosin II function is required to promote bleb formation among gastrula stage mesodermal cells in zebrafish (Weiser et al, 2009) and in Dictyostelium (Sugiyama, Pramanik, & Yumura, 2015), presumably by increasing cortical tension and cytosolic hydrostatic pressure (Tinevez et al, 2009). Bleb formation in Dictyostelium is attributable to the focal disassembly of microtubules that likely stabilize membrane phosphatidylinositol 3,4,5-trisphosphate, a positive regulator of actin assembly (Sugiyama et al, 2015). Myosin phosphatase limits the duration of blebbing among mesodermal cells in zebrafish, thereby allowing transition to intercalative behaviors (Weiser et al, 2009).…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…It was shown that bleb formation is critically dependent on the level of myosin contractility [59]. It also contributes to the extension of blebs by increasing intracellular pressure [86]. Myosin II recruitment to the bleb is thought to drive bleb retraction.…”
Section: Discussionmentioning
confidence: 99%